Differences in information source preferences by students during pre and post PSBB covid-19 pandemic - Darmawan, Mochamad; Handika, Cahyo; Pratama, M. Didan; Al Maulana, M. Aflah (Record and Library Journal, 2021)
Background of Study: The increasingly rapid and massive spread of the COVID-19 virus to various countries, has made the Indonesian Government implement a Large-Scale Social Restriction (PSBB) policy in order to stop the spread of the virus. This policy makes various activities, such as services in libraries, must be closed. This of course makes library users, such as students switch to using electronic information sources. Furthermore, the Government decided to start a new era habit or called the "New Normal" by living adapting to the spread of the virus. Purpose: This research was conducted in order to review the preferences of information sources used by students after the PSBB policy. Method. The research method used is a quantitative approach, with a descriptive type. The target population of this research are students from Surabaya. Data collection was carried out by means of a survey using a questionnaire. Then processed using the SPSS 18.0 application Analysis. The analysis uses theory in the literature. Results: The results showed that most of the students chose electronic information sources as their main preference. This is indicated by the results of research showing that information retrieval machines have become a popular choice both in the pre and post PSBB periods. However, comparative figures show that there are differences in several sources of information in the two periods. Conclusion: Since the PSBB, most students have experienced changes in their preferences for information sources.